(untitled) - Heileman, Gregory L. (New York, 1996)
This textbook provides an in depth course on data structures in the context of object oriented development. Its main themes are abstraction, implementation, encapsulation, and measurement: that is, that the software process begins with abstraction of data types, which then lead to alternate representations and encapsulation, and finally to resource measurement. A clear object oriented approach, making use of Booch components, will provide readers with a useful library of data structure components and experience in software reuse. Students using this book are expected to have a reasonable understanding of the basic logical structures such as stacks and queues.
Keywords: Data structures (Computer science),Computer algorithms,Object-oriented programming (Computer science),Cấu trúc dữ liệu